Ecofeminism Spirituality and Women’s Ecological Leadership in the KCLH Parish Community of St. Paulus, Yogyakarta - Martini, Theresia; Andajani , Sari (Litbang STFT Widya Sasana Malang, 2025)
This study explores women‘s perspectives, experiences, and roles in ecological stewardship through the Community of Love for the Environment (Komunitas Cinta Lingkungan Hidupor KCLH) at St. Paulus Parish, Yogyakarta. Rooted in Catholic ecological values in Laudato Si‟, the community promotes sustainable and faith-based environmental involvement. practices in the parish. Five women, aged 32-60 years participated in in-depth interviews and community observation, and date were analyzed using reflexive thematic analysis. Five interconneted themes emerged:(1) creation care as a form of prayer and spiritual devotion; (2) intergenerational transmission of ecological values; (3) kinship-based caring for the Earth as family; (4) integration of faith and sustainable practices in daily parish life; and (5) collaboration that strengthens solidarity across parish ministries. The findings show how women exercise ecological agency within Church structures by linking spiritual motivations with practical environmental engagement. This study contributes to ecofeminist theological discource by demonstrating how parish-based initiatives can shape understanding of women‘s ecological leadership within Catholic communities.